2012
DOI: 10.2147/opth.s32643
|View full text |Cite
|
Sign up to set email alerts
|

Loteprednol etabonate gel 0.5% for postoperative pain and inflammation after cataract surgery: results of a multicenter trial

Abstract: PurposeLoteprednol etabonate (LE) is approved by the US FDA in a suspension and ointment form (0.5%) for the treatment of postoperative ocular inflammation. This study examined the gel formulation of LE, an improved, nonsettling formulation with a lower preservative level and a more physiologic pH.Patients and methodsThis multicenter, double-masked, parallel-group, vehicle-controlled study randomized patients aged ≥18 years with postoperative anterior chamber cell (ACC) ≥ grade 2 following uncomplicated catara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 20 publications
(26 reference statements)
3
22
0
1
Order By: Relevance
“…6 A 0.5% nonsettling gel formulation of loteprednol etabonate received approval for the treatment of postsurgical inflammation based on randomized placebo-controlled trials that evaluated 14-day use after cataract surgery. 10,11 The purpose of this study was to evaluate the efficacy and safety of loteprednol etabonate 0.5% gel compared with prednisolone acetate 1% suspension when used to prevent immunologic rejection during the first year after DMEK.…”
mentioning
confidence: 99%
“…6 A 0.5% nonsettling gel formulation of loteprednol etabonate received approval for the treatment of postsurgical inflammation based on randomized placebo-controlled trials that evaluated 14-day use after cataract surgery. 10,11 The purpose of this study was to evaluate the efficacy and safety of loteprednol etabonate 0.5% gel compared with prednisolone acetate 1% suspension when used to prevent immunologic rejection during the first year after DMEK.…”
mentioning
confidence: 99%
“…These results are consistent with results from clinical studies with LE ophthalmic gel, 0.5% for the treatment of patients with postcataract pain and inflammation, which reported very few adverse events, mostly related to the surgical procedure itself. 34,35 Most topical steroids are formulated as suspensions, which require vigorous shaking before administration to resuspend the drug. This may be problematic for patients who forget to shake the bottle or do not shake it well enough.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy and safety of LE ophthalmic gel 0.5% were demonstrated in 2 randomized, doublemasked, vehicle-controlled studies in patients following uncomplicated cataract surgery. 34,35 In each study, patients self-administered either LE gel or vehicle 4 times per day for 14 days following surgery. At postoperative Day 8 and 15, a significantly greater proportion of patients treated with LE gel were pain free and had complete resolution of anterior chamber cells compared to patients treated with vehicle (P < 0.001).…”
Section: Introductionmentioning
confidence: 99%
“…No adverse reactions to medications were noted. Furthermore, the authors showed 75.7% of LE-treated patients and 45.8% of vehicle-treated patients had no pain (grade 0) 34. In comparative studies evaluating LE suspension 0.5%, other corticosteroids, or NSAIDs, Stewart found no statistically significant difference in efficacy between the LE- and fluorometholone acetate 0.1%-treated groups.…”
Section: Review Of Efficacy Studiesmentioning
confidence: 98%